Impact of the COVID-19 pandemic on obsessive-compulsive symptoms in the Swiss general population - Otte, Johanna; Schicktanz, Nathalie; Bentz, Dorothée (Frontiers in Psychology, 2023)
Background In the early stages of the COVID-19 pandemic, mental-health experts called attention to a possible deterioration of obsessive-compulsive symptoms (OCSs). In particular, people suffering from a fear of contamination were considered a vulnerable population. Aim The aim of this study was to investigate the change in OCSs from before to during the pandemic within the Swiss general population, and to examine a possible relationship of OCSs to stress and anxiety. Methods This cross-sectional study was implemented as an anonymized online survey (N = 3,486). The Obsessive-Compulsive Inventory-Revised (OCI-R) was used to assess global OCS severity (range: 0–72, clinical cut-off > 18) and specific OCS dimensions (range: 0–12) during the second wave of the pandemic and retrospectively for before the pandemic. Participants were asked to report stress and anxiety in the previous 2 weeks before the survey. Results Participants reported significantly higher OCI-R total scores during (12.73) compared to before the pandemic (9.04, mean delta increase: 3.69). Significantly more individuals reported an OCI-R total score exceeding the clinical cut-off during (24%) than before the pandemic (13%). OCS severity increased on all symptom dimensions, but was most pronounced on the washing dimension (all with p < 0.001). Self-reported stress and anxiety were weakly associated with differences in severity in total score and symptom dimensions (with R2 < 0.1 and p < 0.001). Conclusion Our results indicate that the full spectrum of people with OCS should be considered as risk groups for symptom deterioration during a pandemic and when assessing its possible long-term effects of such.